A Review of Novel Methods To Support The Transition From Methadone and Other Full Agonist Opioids To Buprenorphine/Naloxone Sublingual In Both Community and Acute Care Settings. Issue 4 (December 2019) - Ghosh, Sumantra Monty; Klaire, Sukhpreet; Tanguay, Robert; Manek, Mandy; Azar, Pouya
ABSTRACT: Background: Converting methadone to buprenorphine/naloxone sublingual (SL) is desirable for reasons including ease of prescribing, carries to improving function, decreased drug interactions, and decreased overdose risk. The process of conversion can be difficult given methadone's long half-life and concerns regarding the need for withdrawal before initiation. Purpose: We aim to present several unique methods of converting individuals from methadone and other full opioid agonists (prescribed and illicit) to buprenorphine/naloxone SL as well as describe novel buprenorphine induction protocols to use in community and acute care settings. Methods: A review was conducted using key search databases. Review of publications in peer reviewed journals as well as expert opinions and protocols were used to synthesize this article. Discussion: A description of various protocols, their pros and cons, best setting of use, ease of use, and costs are detailed in the document. Conclusion: Several methods of conversion will provide clinicians with more tools to support transitioning people from methadone and other full agonist opioids to buprenorphine/naloxone SL, as well as reduce withdrawal concerns for buprenorphine induction. Contexte: La conversion de la méthadone en buprénorphine / naloxone sublinguale (SL) est souhaitable pour des raisons telles que la facilité de prescription, entraîne une amélioration du fonctionnement; diminution des interactions médicamenteuses et diminution du risque de surdosage. Le processus de conversion peut être difficile compte tenu de la longévité des effets de la méthadone et des craintes reliées à la nécessité de s'extraire avant l'initiation. Objectif: Nous visons à présenter plusieurs méthodes uniques d'aider des individus à se convertir face à l'utilisation de la méthadone et d'autres agonistes opioïdes complets (prescrits et illicites) en buprénorphine / naloxone SL, et décrivons de nouveaux protocoles d'induction de la buprénorphine à utiliser en milieu communautaire et en milieu de soins de courte durée. Méthodes: Un examen a été effectué à l'aide de recherche clés sur des bases de données. L'examen des publications dans des revues évaluées par des pairs, ainsi que des opinions et protocoles d'experts, ont été utilisés pour synthétiser cet article. Discussion: Le document décrit en détail les divers protocoles, leurs avantages et inconvénients, les meilleurs paramètres d'utilisation, la facilité d'utilisation et les coÛts. Conclusion: Plusieurs méthodes de conversion fourniront aux cliniciens davantage d'outils pour aider les personnes en transition de la méthadone et d'autres opioïdes agonistes complets à la buprénorphine / naloxone SL, ainsi que pour réduire les problèmes de sevrage liés à l'induction de la buprénorphine.